CMV Colitis in Immunocompetent Patients: 2 Cases of a Diagnostic Challenge - Maria Paparoupa; Viola Schmidt; Helgard Weckauf; Huy Ho; Frank Schuppert (Case Reports in Gastrointestinal Medicine)
CMV infections are generally thought to be opportunistic by immunosuppression. Many literature cases though indicate that CMV infections can be also observed in immunocompetent patients. We present an unusual case of an extensive concentric benign stenosis due to CMV colitis and a case of coexistence with Crohn’s Disease, both observed in nonimmunosuppressed individuals. The right diagnosis was set after implementation of multiple unsuccessful treatment strategies. Our purpose is therefore to familiarize clinicians involved with the diagnosis and treatment of gastroenterological diseases with this entity.